Analisis Pelatihan Dan Pengembangan Karyawan - Hasanah Hasanah; Fyo Gebina; Ariva Chafshah; Afif Hammami; Mochammad Isa Anshori (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Human resources are a very important asset for a company in supporting the achievement of company goals, so it is a necessity and necessity for companies to improve employee abilities and competencies through training and development. Training is an effort to increase short-term capabilities, while development is an effort to increase employee competency in preparation for developing higher responsibilities in the future. Human resource development is a systematic and targeted approach to equipping employees in an organization with the skills they need to fulfill job requirements, both on the one hand and on the other hand, a series of planned, implemented and planned activities. This research aims to find out how to analyze development training for employees.